Driving shaft optimizations based on Static Analysis for various material Constriction - Ahmed Salim Naser Almurshedi; Header Ali A; Hussein Awad Kurdi Saad (Genius Journals, 2022)
A significant problematic in the design of a rotating shaft of substantial span is the lateral stability. With light weight composite material it is comparatively simple to meet the strength and torsional stiffness desires utilizing a thin walled tube. The main purpose of this work is to achieve finite element method (FEM) analysis and to find an optimal design of an automobile driving shaft through investigating various composite materials and also to find out compatible and cost-effective. For that, it has been endeavored to recognize the most appropriate composite material which may the alternates instead of classical material of the driving shaft, for that five material have been examined for the same design pattern dimensions and load. These materials are steel alloy as traditional driving shaft material, Kevlar Epoxy, Epoxy carbon, and Epoxy E-Glass. The FEM examination has been prepared all the above material to find out the outstanding material as an alternate material of the driving shaft. The outcomes have discussed that material like Boron-Epoxy can be utilized as an alternate material for the vehicle driving shaft. It has been explored that the Boron-Epoxy is the most promising material instead of predictable material as a result of the maximum static deformation and weight is reduced in comparison to the classical driving shaft material. The weight of the shaft using that material is enhancing to reach about 3.146 kg
Keywords: materials; alternate; Epoxy; examination